I09 Brain glucose hypometabolism in a subject carrying an unstable allele of intermediate CAG33 repeat length in the Huntington's disease gene. (16th November 2010) - Squitieri, F; Esmaeilzadeh, M; Martino, T; Ciarmiello, A
Abstract : Background: It is a general belief that below 36 CAG triplet number, Huntington's disease (HD) does not manifest although unstable transmission of paternal alleles with intermediate length (27–35 CAG repeats) may rarely cause new mutations. However, some recent reports have postulated the association between intermediate allele (IA) length and the development of HD. Aim: We wanted to check whether a subject carrying an unstable IA of 33 CAG repeats (ie, having transmitted a large expansion to his offspring) showed clinical features of HD and/or brain dysfunction. After a careful clinical evaluation assay we performed a brain dynamic quantitative fluoro-deoxy-glucose (FDG) positron emission tomography (PET) scan by using an integrated software (http://www.brainnest.org ). Results: The IA subject showed only subtle and soft neurological signs suggestive of initial HD, such as jerky ocular pursuit, increased latency of saccade initiation, slight arms incoordination. However, in spite of little clinical evidence, the subject showed significant glucose hypometabolism in the caudate, compared with 15 age matched healthy control subjects. Conclusion: Our finding highlights the hypothesis that, in certain conditions, subjects carrying premutations may show an incomplete phenotype including reduced brain glucose uptake and that the abnormal glucose metabolism in the caudate therefore may potentially be a candidate as a premanifest biomarker. The unstable IA may increase the risk to expand in a full mutation not only from a subject to offspring, but also in the nervous system of the same subject, with potential association with HD signs. This should be taken into account during genetic counselling when observing subjects with IAs.